(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This study investigates methods for improving the mesh surface of the SS-15A separator to enhance its efficiency and durability in various separation processes. The mesh surface plays a critical role in the effectiveness of the separator, influencing factors such as particle separation, clogging resistance, and overall performance. Through a combination of material selection, surface treatments, reinforcement techniques, and quality control measures, this research aims to optimize the mesh surface to meet the demands of diverse separation applications. By implementing these enhancements, the SS-15A separator can achieve higher separation efficiency, prolonged service life, and reduced maintenance requirements, leading to improved productivity and cost-effectiveness in industrial settings